The influence of inter-laminar thermal contact resistance on the cooling of material during laser assisted fiber placement. (June 2021) - Çelik, Ozan; Hosseini, S.M. Amin; Baran, Ismet; Grouve, Wouter J.B.; Akkerman, Remko; Peeters, Daniël M.J.; Teuwen, Julie J.E.; Dransfeld, Clemens A.
Abstract: The effect of thermal contact resistance (TCR) correlated to the degree of intimate contact (DIC) between the incoming tape and the substrate on the temperature history during laser-assisted fiber placement (LAFP) was investigated. A novel experimental methodology was designed to understand the effect with a non-contact method which did not influence the local consolidation quality. To assess the influence of TCR numerically, a three-dimensional optical-thermal model was developed. Experimental results indicated that, for the same tape temperature near the nip point, an increase in the compaction force resulted in a decrease in the temperature at the roller exit and the following cooling phase, in correlation with an increase in the final DIC. Also, the effect of the laser power on the final DIC was less pronounced than the compaction force. In the thermal model, when TCR at the tape-substrate interface was not considered, the temperature predictions underestimated the experimental measurements.